On that point! : an introduction to parliamentary debate - Meany, John (International Debate Education Association, 2003)
This is the first parliamentary debate textbook for secondary school students. The text is designed to provide a theoretical and practical foundation for effective participation in parliamentary debate in competition or in the classroom.